Barriers to living kidney donation among relatives of patients with chronic renal failure in south Africa - Mbeje, Pretty; Moleki, Mary; Ganga-Limando, Makombo (International Journal of Advanced Nursing Studies, 2014)
Background: The number of patients with chronic renal failure awaiting kidney transplantation has been increasing in the country. There is a great awareness regarding the importance of kidney donation among family members and the public at large. But little is known about their reluctance to donate kidney. Aim: The aim of this study was to explore and describe barriers to living kidney donation among relatives of patients with chronic renal failure undergoing haemodialysis in one of the provinces in South Africa. Methods: The study used qualitative, descriptive, exploratory and contextual design. Purposive sampling was carried out to select close family members and relatives of patients undergoing haemodialysis. Data was collected through individual face to face in-depth interviews with 25 participants. Interviews were recorded and analysed using thematic content analysis approach. Results: This study identified six major barriers to living kidney donation among relatives of patients with chronic renal failure undergoing haemodialysis. They included: cultural beliefs, mistrust, fear, lack of information, being old, and pre-existing medical conditions. These barriers are well documented in the literature. Conclusion: The study has direct implication for the quality of life of patients with chronic renal failure. Kidney transplantation is associated with drastic improvements in survival and quality of life as well as considerable cost savings, compared with haemodialysis or peritoneal dialysis. It cannot be achieved without organ donors. Therefore, extensive public education aimed at ad-dressing factors restraining people to donate organ is needed.   Keywords: Barriers to Kidney Donation, Chronic Renal Failure, Haemodialysis, Patients’ Relatives, South Africa.